Fostering Islamic leadership character through hizbul wathan extracurricular activities: evidence from Muhammadiyah school in Indonesia - Hidayah, Anis Nur; Puspitasari, Ika; Arifin, Shokhibul (UIR Press, 2026)
The formation of students' leadership character is one of the primary goals of character education within Muhammadiyah schools, particularly through Hizbul Wathan (HW) extracurricular activities. This study aims to analyze the role of Hizbul Wathan extracurricular activities in shaping the leadership character of students at SMK Muhammadiyah 1 Surabaya, with a focus on the contribution of HW activities, the role of instructors, and the supporting and inhibiting factors in program implementation. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis involving instructors, student administrators, and active HW members, who were selected using purposive sampling technique. Data were analyzed using thematic analysis with source and technique triangulation to ensure data validity. The research findings indicate that HW activities such as marching drills, camping, scouting training, and leadership exercises make a tangible contribution to shaping students' leadership character through direct field experiences. Instructors play a role not only as technical guides, but also as motivators and role models who encourage the internalization of Islamic-based leadership values. The originality of this study lies in its in-depth examination of HW's role specifically at the vocational high school level, which has thus far remained rarely investigated empirically. The limitations of this study include a scope restricted to a single school, meaning that generalization of the findings must be carried out with caution. The implications of this research provide practical recommendations for schools in optimizing the management of HW programs as an effective, purposeful, and sustainable vehicle for the formation of student leadership.